A Stepwise Approach to the "Frozen Neck" for Secondary Microsurgical Reconstruction. Issue 10 (4th October 2021) - Chicco, Maria; Huang, Tony Chieh-Ting; Lee, Min-Min; Cheng, Hsu-Tang
Abstract : Supplemental Digital Content is available in the text.